2, 3
3, 2
-2, -3
-3, -2
Correct answer is C
log4(y - 1) + log4(12x) = 1
log4(y - 1)(12x) → (y - 1)(12x) = 4 ........(1)
log2(y + 1) + log2x = 2
log2(y + 1)x = 2 → (y + 1)x = 22 = 4.....(ii)
From equation (ii) x = 4y+1........(iii)
put equation (iii) in (i) = y (y - 1)[12(4y−1)] = 4
= 2y - 2
= 4y + 4
2y = -6
y = -3
x = 4−3+1
= 4−2
X = 2
therefore x = -2, y = -3
Find the area of an equivalent triangle of side 16cm ...
Simplify 3n−3n−133×3n−27×3n−1...
Evaluate x2(x2 - 1)-12 - (x2 - 1)12...
A rectangle has length xcm and width (x - 1)cm. If the perimeter is 16cm. Find the value of x ...
What is the locus of point that is equidistant from points P(1,3) and Q(3,5)? ...
Tanθ is positive and Sinθ is negative. In which quadrant does θ lies ...
The volume of a cube is 512cm3. Find the length of its side...